(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Daily conversation is an essential component of human connection, promoting the flow of information, emotions, and social bonds. The scientific examination of such talks sheds light on the underlying processes and dynamics that control dialogic interactions. This article examines the techniques and results of scientific study on ordinary conversation, emphasizing how these encounters change and grow within the framework of dialogic communication.